2015
DOI: 10.4269/ajtmh.15-0332
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Virus Infections Among Patients with Dengue-Like Illness at a Tertiary Care Hospital in the Philippines, 2012–2013

Abstract: Abstract. Chikungunya virus (CHIKV) often co-circulates with dengue virus (DENV). A cross-sectional surveillance study was conducted at a tertiary hospital in Manila, Philippines, to describe the prevalence and characteristics of DENV and CHIKV infections among patients seeking care for dengue-like illness. Acute blood samples from patients ≥ 6 months of age clinically diagnosed with dengue from November 2012 to December 2013 underwent reverse transcription polymerase chain reaction (RT-PCR) to detect DENV and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
0
16
0
4
Order By: Relevance
“…En Yemen, en el año 2012, un estudio reportó co-infección de 2,3% 35 . Para el período 2012 y 2013, en Filipinas se identificó la co-infección en 11 casos (10%) a partir de 112 pacientes con diagnóstico de dengue por reacción de polimerasa en cadena (RPC) 36 . En Nepal, para los mismos años, se analizaron 169 muestras de todos los pacientes febriles al ingreso de varios hospitales y se halló la co-infección en cinco casos (5,0%) 37 .…”
Section: Infectología Al Díaunclassified
See 2 more Smart Citations
“…En Yemen, en el año 2012, un estudio reportó co-infección de 2,3% 35 . Para el período 2012 y 2013, en Filipinas se identificó la co-infección en 11 casos (10%) a partir de 112 pacientes con diagnóstico de dengue por reacción de polimerasa en cadena (RPC) 36 . En Nepal, para los mismos años, se analizaron 169 muestras de todos los pacientes febriles al ingreso de varios hospitales y se halló la co-infección en cinco casos (5,0%) 37 .…”
Section: Infectología Al Díaunclassified
“…Siete estudios no exponen con claridad el cuadro clínico de los pacientes con co-infección en comparación con los pacientes con mono-infección por DENV o CHIKV 26,34,[36][37]39,41,53 . Dos artículos en La India y uno en Guatemala presentan con mayor precisión el cuadro clínico de los pacientes co-infectados.…”
Section: Manifestaciones Clínicas De La Co-infección Denv-chikvunclassified
See 1 more Smart Citation
“…According to historical records, CHIKV is likely to have been present since 1779 [10]. However, due to the similar clinical manifestations between CHIKV and dengue infections, CHIKV-infected patients were likely to have been initially misdiagnosed as having dengue infection [10,11]. CHIKV was first isolated and identified during an outbreak in Tanzania in 1953 [4].…”
Section: Introductionmentioning
confidence: 99%
“…14 Velasco JM et al found many Chikungunya Virus among Patients with Dengue-Like Illness. 15 This emphasizes the need for a routine and differential diagnosis of arboviruses in patients with dengue-like illness. Unfortunately, laboratory assays, such as real-time reverse transcription polymerase chain reaction, virus cDNA sequencing, and enzyme-linked immunosorbent assay are not easily available.…”
mentioning
confidence: 99%